2011
DOI: 10.1016/j.dsr2.2010.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution and shape properties of relatively small sea-ice floes in the Antarctic marginal ice zone in late winter

Abstract: In the marginal sea ice zone (MIZ), where relatively small ice floes are dominant, the floe size distribution is an important parameter affecting melt processes given the larger cumulative perimeter of multiple small floes compared with a single ice floe of the same area. Smaller ice floes are therefore subject to increased lateral melt. However, the available data have been very limited so far. Analysis of sea ice in the Sea of Okhotsk revealed that while floe size distribution is basically scale invariant, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
218
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(240 citation statements)
references
References 34 publications
16
218
0
Order By: Relevance
“…p(D|D max > 200 m) = δ(D − 200 m). This latter assumption is somewhat vestigial but was related to the fact that wavelengths that break in the ice are usually less than about 400 m. The rest of our approximation is similar to the FSD used by Dumont et al (2011), which was based on the renormalisation group (RG) approach to the same problem, used by Toyota et al (2011). However, this formula made the mean floe size a discontinuous function of the maximum floe size, so we have modified it to a continuous (as opposed to discrete) FSD -a power-law-type probability density function p(D) truncated at D = D max , but with the same exponent as before:…”
Section: Floe-size Distributionmentioning
confidence: 87%
See 2 more Smart Citations
“…p(D|D max > 200 m) = δ(D − 200 m). This latter assumption is somewhat vestigial but was related to the fact that wavelengths that break in the ice are usually less than about 400 m. The rest of our approximation is similar to the FSD used by Dumont et al (2011), which was based on the renormalisation group (RG) approach to the same problem, used by Toyota et al (2011). However, this formula made the mean floe size a discontinuous function of the maximum floe size, so we have modified it to a continuous (as opposed to discrete) FSD -a power-law-type probability density function p(D) truncated at D = D max , but with the same exponent as before:…”
Section: Floe-size Distributionmentioning
confidence: 87%
“…where γ = 2+log f/ log ξ , f is the fragility in the RG formulation of Toyota et al (2011), and ξ 2 is the number of pieces formed during each successive break-up in the same RG formulation. We use D min = 20 m, f = 0.9 and ξ = 2, making γ ≈ 1.84.…”
Section: Floe-size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these facts do not affect the general conclusions formulated above. The present results agree with the findings of Squire et al (1995), described in the introduction, and provide another evidence -obtained with a very different model than that of Squire and colleagues -in favor of the hypothesis that it is the ice itself (its thickness and strength) and not the incident waves that decide upon the dominating floe size in MIZ, at least during the initial stages of ice breaking (at later stages, many other factors lead to further fragmentation of ice floes, producing wide, heavy-tailed FSDs typically observed in inner parts of MIZ; see, e.g., Toyota et al, 2011Toyota et al, , 2016, and references there). In particular, it is worth stressing that in terms of the floe size resulting from breaking, the results are not sensitive to the modeled attenuation rates of wave energy (which, as already mentioned in Sect.…”
Section: Discussionmentioning
confidence: 99%
“…The exponent α has been commonly estimated by fitting a straight line on a log-log plot (for either FND or CFND) using least-square fit (LSF) (e.g., Rothrock and Thorndike, 1984;Toyota et al, 2011 and2006;Wang et al, 2016;Stern et al, 2017a and2017b). A recent study by Clauset et al (2009) and Virkar and Clauset (2014) suggested a method to calculate the exponent α for any given dataset by using the maximum likelihood estimator.…”
Section: Research Articlementioning
confidence: 99%